PENGABDIAN DALAM MENGOPTIMALISASIKAN PENGOLAHAN LIDI KELAPA UNTUK MENINGKATKAN PEREKONOMIAN MASYARAKAT DI DESA PENAGA - Agusven, Tubel; Fatahuddin, Fatahuddin; Taher, Indra Bastian; Audyanto, Regi; Amadeah, Chelsa Teyora; Destanis, Shakira Qodima; Agustuti, Sela Julia; Purwanti, Dian Eka; Santoso, Bima Maulana (Jurnal Pengabdian, Pembelajaran dan Pemberdayaan Ekonomi Masyarakat (JP3EM), 2025)
Coconut tree is a plant that has many benefits. Almost all parts of this tree can be used, such as the fruit which is rich in nutrients, the skin can be used as a container or charcoal and the leaves can be used as a broom stick. Despite its many benefits, the waste of coconut trees is often neglected by the community. Lots of coconut trees are left and not utilized. The objectives to be achieved in this activity are: 1. Fostering the entrepreneurial interest of the Penaga Village community in processing coconut sticks through a socialization program, 2. Improving the skills of the Penaga Village community in processing coconut sticks through a training program, 3. Increasing people's income through processing coconut sticks . This method uses a qualitative method because interviews were conducted with the village head and continued with the entrepreneurship outreach program and coconut stick processing training.